Respondents versus Informants Methods of Data Collection: Implications for Business Research - Singh, RBN; Hassan, Arif (2012)
The paper is based on a study that compares data collected from two methods, namely, individuals acting as respondents and individuals acting as informants. The former involves self-rating while the later asks individuals to rate other’s beliefs, preferences, and actions. The study objective was to examine the role of social desirability factor in self-rating method of data collection. Good number of business and management studies uses self-rating questionnaires and interviews which may not yield data that truly reflect the reality due to respondents’ tendency to present himself/herself in a socially desirable manner. This may be even more pronounced in a collectivistic culture where individual’s thoughts and perception are deeply influenced by the social norms and values. No such study has been conducted that compares the two method of data collection in a single study, providing the justification for this research. A sample of 100 adults of mix background from India and 127 students from Malaysia rated predominantly positive and negative description of beliefs, values and preferences twice--first for the people residing around them and then for themselves. They also rated themselves on a scale of social desirability. The findings confirmed that the respondents attributed negative cognitions (beliefs, values and preferences) to the people more than themselves. They attributed predominantly positive beliefs, values and preferences to themselves and people, although a shade more to themselves. The social desirability orientation was meaningfully related to respondents’ self but not to people’s related perceptions. The findings thus favored the use of respondents in informants’ role of judging people’s cognitions of social reality.